(untitled) (Bangladesh Journal of Botany, 2024)
This paper deal with the analysis of the relationship between acidity and alkalinity with organic carbon structure and humus components of tobacco-growing soils in Tengchong city. Under the same level of organic matter and nutrient content, soils with different pH values in Tengchong city were selected for the investigation. Results showed that the HA/FA values of the soil with low organic matter content gradually decreased with increasing pH, indicating a higher content of active carbon components and a lower content of stable carbon components in the soils. In soils with high organic matter content, pH value showed a highly significant negative correlation with HA/FA and PQ values. With increasing acidity, HA/FA became higher, and humus components with high stability increased. At the same level of organic matter content, the infrared A2920/A1630 ratio gradually increased with increasing pH. It indicates that at a certain pH range and the same level of organic matter content, the stable humus component increases, and the soil pH value decreases. Bangladesh J. Bot. 53(3): 745-755, 2024 (September) Special